Do video sounds interfere with auditory event-related potentials? - McArthur, G; Bishop, D; Proudfoot, M (Springer-Verlag, 2003)
To make the electroencephalogram (EEG) recording procedure more tolerable, listeners have been allowed in some experiments to watch an audible video while their auditory P1, N1, P2, and mismatch negativity (MMN) event-related potentials (ERPs) to experimental sounds have been measured. However, video sounds may degrade auditory ERPs to experimental sounds. This concern was tested with 19 adults who were instructed to ignore standard and deviant tones presented through headphones while they watched a video with the soundtrack audible in one condition and silent in the other. Video sound impaired the size, latency, and split-half reliability of the MMN, and it decreased the size of the P2. However, it had little effect on the P1 or N1 or on the split-half reliability of the P1-N1-P2 waveform, which was significantly more reliable than the MMN waveform regardless of whether the video sound was on or off. The impressive reliability of the P1 and N1 components allows for the use of video sound during EEG recording, and they may prove useful for assessing auditory processing in listeners who cannot tolerate long testing sessions.